Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Merger Akuisisi pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia - Nur Qoni'ah; Riskin Hidayat (Universitas Islam Kadiri, 2023)
This study aims to examine the differences in the financial performance of non-financial companies before and after mergers and acquisitions listed on the Indonesia Stock Exchange. The company's financial performance is measured by four financial ratios. The financial ratios used are the liquidity ratio proxied by the current ratio, the solvency ratio is proxied by the debt ratio, the activity ratio is proxied by total asset turnover, the profitability ratio is proxied by the net profit margin. The data analysis technique used in this study used the paired sample t-test analysis and the normality test. The data collection technique uses documentation techniques, the source of data in this study is secondary data and the type of data is documentary data. This study took a sample of non-financial companies that carried out merger acquisitions in 2016-2018 which were listed on the Indonesia Stock Exchange. Determination of the sample using purposive sampling method and obtained a sample of 14 companies. This study uses a window period of three years before and three years after merger acquisition. The results of this study indicate that there is a significant difference in Total Asset Turnover before and after the acquisition merger, while there is no significant difference in the Crrent Ratio, Net Profit Margin, Debt Ratio before and after the acquisition merger.